Psychosocial job stressors and risk of suicidal behavior - an observational study among Swedish men - Maria Åberg; Elisabeth Staats; Josefina Robertson; Linus Schiöler; Kjell Torén; Anthony D LaMontagne; Mia Söderberg; Margda Waern; Jenny Nyberg (Nordic Association of Occupational Safety and Health (NOROSH), 2022)
OBJECTIVE: This study aimed to explore the relationship between psychosocial job stressors and suicidal behavior (fatal and non-fatal) among Swedish men while controlling for potential confounders. METHODS: Population-based Swedish longitudinal cohort study of male conscripts without previous self-harm (N=1 483 310) enlisting 1968-2002. Conscription examinations included measures of IQ, stress resilience and psychiatric diagnoses. Job demand-control (JDC) exposure was assessed using the Swedish Job Exposure Matrix linked to specific occupations. Suicidal behavior among men aged 30-64 was identified in the National Hospital Register (non-fatal self-harm) and Swedish Cause of Death Register (suicide) during follow-up 2002-2014. Cox regression models were used to estimate associations between JDC category and suicidal behavior. RESULTS: In fully adjusted models, passive jobs (low demand-low control) showed the highest risk of suicidal behavior [hazard ratio (HR) 1.33, 95% confidence interval (CI) 1.25-1.43] compared to those with low strain (low demand-high control), followed by high strain (high demand-low control) (HR 1.12, 95% Cl 1.03-1.22). A lower risk of suicidal behavior was found in the active category, where levels of both demand and control are high (HR 0.64, 95% Cl 0.60-0.70). Separate analyses for suicide as outcome revealed a lower risk of suicide in persons with active jobs (high demands-high control). The passive category showed a higher risk for suicide, but the association did not remain after adjustment for stress resilience and IQ. CONCLUSIONS: These results show that psychosocial job stressors among men are associated with risk for suicidal behavior. Improving job control has the potential to decrease suicidal behavior for this group.